Major and trace element characteristics of apatites in granitoids from central Kazakhstan: Implications for petrogenesis and mineralization - Cao, Mingjian; Li, G.; Qin, K.; Seitmuratova, E.; Liu, Y. (Society of Resource Geology, 2012)
This paper presents abundances of major and trace elements of apatites in granitic rocks associated with different types of ore deposits in Central Kazakhstan on the basis of electron probe microanalysis and laser ablation inductively coupled plasma mass spectrometry. Our results demonstrate that the concentrations and ratios of elements in apatites from different granitoid rocks show distinct features, and are sensitive to magma evolution, petrogenetic and metallogenetic processes. Apatites in the rocks associated with Mo-W deposits have high content of F and MnO, low content of Cl, which may be indicative of sedimentary sources, while apatites from a Pb-Zn deposit show relatively high content of Cl and low F content, which possibly suggest a high water content. In these apatites, Sr contents decrease, while Mn and Y contents increase with magma evolution. This relationship reflects that these elements in apatites are related with the degree of magmatic differentiation. Four types of REE patterns in apatites are identified. Type 1 character of highest (La/Yb) N in apatites of Aktogai porphyry Cu-Mo deposit, Sayak-I skarn Cu deposit and Akzhal skarn Pb-Zn depposit is likely produced by the crystallization of heavy REE-enriched minerals. Type 2 character of upward-convex light REE in apatite of Aktogai porphyries likely results from La-enriched mineral crystallization. Type 3 feature of Nd depletion in apatites of East Kounrad and Zhanet deposits both from Mo-W deposits primarily inherits the character of host-rock. Type 4 apatites of Aktogai deposit and Akshatau W-Mo deposit with wide range of REE contents may suggest that apatites crystallize under a wide temperature range. Three types of apatite with distinct redox states are identified based on Eu anomaly. The Aktogai apatite with slight negative Eu anomaly displays the most oxidized state of the magma, and the apatites of other samples at Aktogai, East Kounrad and Akzhal with moderate negative Eu anomaly show moderate oxidizing condition of these rocks, while the remaining apatites with strong En anomaly indicate a moderate reductive state of these rocks. © 2011 The Authors. Resource Geology © 2011 The Society of Resource Geology.